ORAL MICROBIOME AND THE PERIODONTITIS-CARDIOVASCULAR DISEASE AXIS: INFLAMMATORY, MICROBIAL, AND METABOLIC MECHANISMS - Vera Santos Gumert, Jennifer; Leandro da Conceição , Aléxia Caroline; Pinheiro Sperandio, José Augusto; Cesar Soares, Christian; de Oliveira Ribeiro, Samara; Azevedo Moraes de Brito, Gabriela; Chaves Campos de Amaral, Ediliana Dias; Justo Bellafronte Rique, Ana Caroline; Mendes , Nathalia Amorim Braga (Periódicos Brasil. Pesquisa Científica, 2026)
Periodontitis is a chronic multifactorial inflammatory disease associated with oral biofilm dysbiosis and progressive destruction of tooth-supporting tissues. Increasing evidence suggests that its impact extends beyond the oral cavity and may contribute to systemic diseases, particularly cardiovascular diseases (CVD). In recent years, the oral microbiome has emerged as a biologically plausible mediator linking periodontal inflammation to atherosclerosis, endothelial dysfunction, systemic inflammation, and cardiometabolic disturbances. This study aimed to review recent literature on the oral microbiome–periodontitis–cardiovascular disease axis, focusing on inflammatory, microbial, and metabolic mechanisms. A narrative literature review was conducted using PubMed-indexed studies published between 2021 and 2026. The evidence indicates that oral dysbiosis and periodontitis may contribute to transient bacteremia, systemic cytokine release, endothelial activation, immune dysregulation, and microbial metabolite production with potential pro-atherogenic effects. Key pathogens such as Porphyromonas gingivalis, Fusobacterium nucleatum, and Tannerella forsythia have been associated with vascular inflammation, oxidative stress, platelet activation, and lipid dysregulation. Furthermore, recent studies suggest that oral microbiome signatures may serve as non-invasive biomarkers for cardiovascular risk prediction. It is concluded that the oral microbiome–cardiovascular axis represents an emerging and clinically relevant field in contemporary periodontology, with promising translational implications for prevention, diagnosis, and integrated care.